VOCATIONAL-PEDAGOGICAL EDUCATION IN RUSSIA: HISTORICAL AND LOGICAL PERIODS - V. A. Fedorov; N. V. Tretyakova (Образование и наука)
Introduction. Rapid social and economic changes demand new methods and forms of vocational training, reorganization of content of professional education, i.e. its modernizations which cannot be carried out without existence of the qualified pedagogical staff. Therefore, high-quality professional and pedagogical preparation becomes today not just one of education components, and, without exaggeration, a guarantee of social and economic wellbeing of the country. To provide due functioning of the system of vocational pedagogical education (VPE), it is necessary to understand its specifics and regularities of development; thus, it is necessary to track formation and evolution of the system.The aim of the study is to provide retrospective analysis at the organizational and substantial level of development of VPE in Russia as the social and pedagogical system.Methodology and research methods. The historical and logical approach has become the leading approach while researching the problems of VPE. It allows us to build the accurate sequence of formation of the system of training of teachers of specific disciplines and masters of vocational training; on this basis to reveal its shortcomings and possibilities.Results and scientific novelty. A brief background into history of the Russian and foreign vocational pedagogical education existing prior to the beginning of the 20th century is given. The chronology of development of VPE in Russia since 1920-s till modern period is presented. According to the key changes happening in a target and organizational-content part of VPE, six stages are distinguished and described. It is shown that development of this type of education as a social and pedagogical system is caused by socio-economic factors and administrative decisions; at the same time the VPE system has own regularities, principles of functioning and internal potential for further improvement.The relevance of the appeal to VPE history is emphasized. The reflection concerning the accumulated positive and negative experience: promotes more exact diagnostics of tendencies in this area; helps to avoid former mistakes and to level the existing contradictions; enables to choose the most effective strategy of development of VPE.Practical significance. The materials of the publication can be useful for scientific and practical workers who are taking part in training of teachers of vocational education and engaged in forecasting and design of development of the system of vocational pedagogical education.